2007
DOI: 10.1007/s10163-007-0178-9
|View full text |Cite
|
Sign up to set email alerts
|

European Union waste management strategy and the importance of biogenic waste

Abstract: In the European Union (EU), waste management is almost totally regulated by EU directives, which supply a framework for national regulations. The main target in view of sustainability is the prevention of direct disposal of reactive waste in landfi lls. The tools to comply with these principles are recycling and material recovery as well as waste incineration with energy recovery for fi nal inertization. The adaptation of the principles laid down in EU directives is an ongoing process. A number of countries ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 0 publications
0
17
1
2
Order By: Relevance
“…It is important to underline that material recovery and thermal treatment are two strategies that may be adopted together, not in competition. Vehlow et al (2007) have in fact shown that EU member states that extensively practice material recovery (including composting) also incinerate a major part of their residual waste. The correlation between high recycling rates and the adoption of waste-to-energy treatments for commingled residual waste was also evidenced in a recent study (Castaldi and Themelis, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to underline that material recovery and thermal treatment are two strategies that may be adopted together, not in competition. Vehlow et al (2007) have in fact shown that EU member states that extensively practice material recovery (including composting) also incinerate a major part of their residual waste. The correlation between high recycling rates and the adoption of waste-to-energy treatments for commingled residual waste was also evidenced in a recent study (Castaldi and Themelis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Vehlow et al (2007) calculated the potential of residual MSW to replace fossil fuels in the power market of selected EU countries and found values ranging from 3% to 5% for countries such as Germany and Italy. These figures may be deemed interesting also in consideration of the fact that the biogenic fraction of MSW accounts for more than 50-60% of its energy inventory and hence more than half the CO 2 emitted from the combustion of MSW may be regarded as climate neutral (Vehlow et al, 2007;Castaldi and Themelis, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hardness values of blades made of steel scrap SS2 and SS4 were lower, 34 HRC and 43 HRC, respectively. By reusing steel scrap for different purposes various benefits can be achieved (reduction costs, saving energy, less raw material usage and decrease in waste disposal costs), which is in accordance to the basic requirements of the European Union waste management strategy (Vehlow et al, 2007). Figure 9.…”
Section: Conclusionesmentioning
confidence: 63%
“…Instead, mechanical, biological, and/or thermal treatment measures have to be carried out before final disposal. This is the result of a planned waste management strategy initiated by the Government more than 20 years ago [2], of which the fundamental objectives are (a) the reduction of waste generation, (b) the prohibition of uncontrolled discarding, discharge, and disposal of waste, and (c) the promotion of integrated waste management systems following the steps: avoidance, recycling, and conversion of waste with a preference to material and energy recovery [2].…”
Section: Introductionmentioning
confidence: 99%